Markets in Fashion : a Phenomenological Approach. - Aspers, Patrik, 1970- (Taylor & Francis, 2005)
This book is an analysis of the economics of the fashion photography industry. Aspers shows how photographers gain their identity in the market and how markets are constructed at the interface of economy and art.